Estudio de factibilidad para la creación de un centro de acopio de maíz (Zea Mayz) para disminuir pérdidas poscosecha en las Comunidades de la Parroquia Licto - Pilataxi Yungan, Edison Ivan (2021)
This document provides a feasibility study for the creation of a corn collection center to reduce post-harvest losses in the communities of the Licto parish. In the first instance, the demand for soft white corn and beans is analyzed, then the necessary investment and its financing are presented. Secondly, the cost structure is determined, defining its fixed and variable costs that incur in the production, administration and commercialization of the project. In addition, the financial evaluation is performed according to the indicators such as NPV is $ 16,771.46 positive, the IRR with 10% is greater than the TMAR, the cost benefit is $ 1.09, which corresponds to what is available for each dollar invested one dollar to pay and 0.9 cents to win. Finally, the capital recovery period is 4 years with 10 months for this project. Therefore, the creation of a corn collection center in the Licto parish is feasible